Automation Process in Emerging World and its importance - Ragavendra. K (International Journal on Orange Technologies, 2019)
The report is based on the automation process in the emerging world. As the world is growing towards the automation process, all these industries are utilizing the benefits of automation in the working process. With the help of a new automation technique, the working procedures are performing very fast and effectively. To use automation we just need a computer or a system. Some artificial software tools are there that need to be installed in the computers so the machine can perform the task. It gives us the benefit of fast operations. So automation and digital technology also be a blessing for total countries as they could conduct to receive in productivity which is finally the driver of improvement